(untitled) (Journal of Geography and Environmental Management, 2018)
The article discusses the scientific approach in studing of management in eco-tourism, researching features and perspectives in the field of our country. The structural elements of management in ecotourism, the impact of state planning and management to environment, and the role of marketing in the promotion of a positive image of tourist facilities have been identified.